Wide bandgap BaSnO3 films with room temperature conductivity exceeding 104 S cm−1 - Prakash, Abhinav (2018)
Wide bandgap perovskite oxides with high room temperature conductivities and structural compatibility with a diverse family of organic/inorganic perovskite materials are of significant interest as transparent conductors and as active components in power electronics. Such materials must also possess high room temperature mobility to minimize power consumption and to enable high-frequency applications. Here, we report n-type BaSnO3 films grown using hybrid molecular beam epitaxy with room temperature conductivity exceeding 104 S cm−1. Significantly, these films show room temperature mobilities up to 120 cm2 V−1 s−1 even at carrier concentrations above 3 × 1020 cm−3 together with a wide bandgap (3 eV). We examine the mobility-limiting scattering mechanisms by calculating temperature-dependent mobility, and Seebeck coefficient using the Boltzmann transport framework and ab-initio calculations. These results place perovskite oxide semiconductors for the first time on par with the highly successful III–N system, thereby bringing all-transparent, high-power oxide electronics operating at room temperature a step closer to reality.